2022
DOI: 10.53730/ijhs.v6ns2.8856
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening awareness among expatriates’ adults living in Saudi Arabia

Abstract: Background: Cancer is the second major cause of death worldwide. Early detection of cancer is a cornerstone of cancer survival. Cancer of the prostate is a major cause of concern for all men, as it offers a serious health risk, particularly to human males over 40 years. The main aim of the current study was to determine the level of awareness of prostate cancer screening among expatriates’ adults living in Saudi Arabia. Methods: A prospective cross-sectional study was used during March 2020 and January 2021; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The number of women employed in Saudi healthcare remains low, with statistics showing pharmacists, dentists, physicians, or allied personnel as comprising 37%, 36.4%, 36.3%, and 24.4%, respectively, of the entire workforce. 20 It is only in nursing that the majority of women are employed, which comprises 61.8%. 20 Nonetheless, although the number of women being employed in Saudi healthcare is increasing, 12 , 18 , 19 there is evidence of gender disparities in wages or salaries and allowances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of women employed in Saudi healthcare remains low, with statistics showing pharmacists, dentists, physicians, or allied personnel as comprising 37%, 36.4%, 36.3%, and 24.4%, respectively, of the entire workforce. 20 It is only in nursing that the majority of women are employed, which comprises 61.8%. 20 Nonetheless, although the number of women being employed in Saudi healthcare is increasing, 12 , 18 , 19 there is evidence of gender disparities in wages or salaries and allowances.…”
Section: Introductionmentioning
confidence: 99%
“… 20 It is only in nursing that the majority of women are employed, which comprises 61.8%. 20 Nonetheless, although the number of women being employed in Saudi healthcare is increasing, 12 , 18 , 19 there is evidence of gender disparities in wages or salaries and allowances. For instance, a report by the World Economic Forum indicates that Saudi Arabia ranks 127th out of 146 countries in terms of equal pay, which is confirmed by Stoeger et al’s study that found significant gender pay disparities.…”
Section: Introductionmentioning
confidence: 99%